Faktor-faktor yang Mempengaruhi Produktivitas Usahatani Kopi Arabika di Desa Catur Kecamatan Kintamani Kabupaten Bangli (Jurnal Agribisnis dan Agrowisata, 2025)
Factors Affecting the Productivity of Arabica Coffee Farming in Catur Village, Kintamani District, Bangli Regency. Catur is one of the Arabica coffee-producing villages in Kintamani, Bangli. The agricultural land in Desa Catur is managed by eight subak groups distributed in each hamlet. Subak Abian Wanasari Kenjung is one of the subak groups located in Desa Catur, Kintamani, Bali. This subak group engages in integrated farming activities, cultivating coffee plants, oranges, and raising cattle. The predominant coffee type cultivated is Arabica coffee. The purpose of this study is to analyze the level of productivity and identify the factors influencing coffee farming productivity in Desa Catur. The coffee productivity achieved by farmers in Subak Abian Wanasari Kenjung reaches 2,939 kg/ha of red cherries. The studied productivity factors include capital, plant age, and farming experience. The research results indicate that capital has a positive and significant impact on coffee productivity. Every 1% increase in invested capital leads to a 0.191 increase in productivity. Plant age also has a positive and significant effect on productivity. Each increase in plant age results in a productivity increase of 0.436. Furthermore, farming experience also exhibits a positive and significant influence on productivity. All three of these factors collectively play a crucial role in enhancing Arabica coffee farming productivity in Desa Catur. In efforts to boost productivity, farmers need to consider efficient capital management, pay attention to optimal plant age, and continually develop farming experience and skills.
Keywords: arabica coffee; productivity factors; multiple linear regression; quantitative data; farming